1975
DOI: 10.1111/j.1365-2494.1975.tb01381.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Botanical Composition of Oesophageal Extrusa Samples. 1. A Modified Microscope Point Technique

Abstract: Extrusa samples were collected from oesophageally fistulated sheep that had been fed mixtures of known proportions of a legume and a grass. The botanical eomposition of these samples was estimated by two microscope point techniques. When estimates were made by recording hits on eaeh species the legume content of the ingesta was eonsistently underestimated by up to 23%. Much of this underestimate was attributed to the weight per unit area of the leaves of the legume being approximately twice that of the grass l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1975
1975
1998
1998

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The proportions of the four main plant parts (pseudostem, dead stem, dead leaf and sheath and green leaf) in the extrusa and sward samples were calculated as proportions of the total OM weight less the OM weight contributed by inflorescence and non-grass species; the proportion of green leaf in the extrusa was corrected taking into account the OM weight of the liquid fraction of the extrusa minus a fixed amount of 3·6 mg OM ml Ϫ1 contributed by saliva, according to the procedure of Hamilton and Hall (1975). This procedure homogenized the data and allowed the relationships between the proportions of plant parts in the diet and those in the grazed horizon of the sward to be studied as, although the amounts of inflorescence and non-grass species in the sward were undetectable, some extrusa samples contained a small proportion (< 0·05) of these plant parts.…”
Section: Animalsmentioning
confidence: 99%
“…The proportions of the four main plant parts (pseudostem, dead stem, dead leaf and sheath and green leaf) in the extrusa and sward samples were calculated as proportions of the total OM weight less the OM weight contributed by inflorescence and non-grass species; the proportion of green leaf in the extrusa was corrected taking into account the OM weight of the liquid fraction of the extrusa minus a fixed amount of 3·6 mg OM ml Ϫ1 contributed by saliva, according to the procedure of Hamilton and Hall (1975). This procedure homogenized the data and allowed the relationships between the proportions of plant parts in the diet and those in the grazed horizon of the sward to be studied as, although the amounts of inflorescence and non-grass species in the sward were undetectable, some extrusa samples contained a small proportion (< 0·05) of these plant parts.…”
Section: Animalsmentioning
confidence: 99%
“…Samples were collected each morning and evening, over a 30-min period; these were bulked and a subsample was taken to determine botanical composition using the microscopic point technique of Hamilton and Hall (1975).…”
Section: Measurementsmentioning
confidence: 99%
“…The botanical composition of ingested herbage was determined using extrusa samples collected from the oesophageally fistulated sheep. Samples were collected each morning and evening, over a 30-min period; these were bulked and a subsample was taken to determine botanical composition using the microscopic point technique of Hamilton and Hall (1975).…”
Section: Measurementsmentioning
confidence: 99%
“…The extrusa were squeezed in muslin to separate the solid and liquid fractions. The botanical composition of a 24 g sub-sample ofthe solid was estimated by the microscope point technique in which hits were adjusted by WAC based on fresh herbage (3). A second sub sample was separated manually after being divided into four replicates of 6 g. Each replicate was agitated in distilled water and was dispersed on 3 filter papers in the same manner as the samples that were observed under the microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Hamilton and Hall (3) have shown that the accuracy of the microscope point technique can be improved by adjusting the microscope hits for the weight per unit area of the various plant components. In the present experiment, estimates of botanical composition were made by manual separation and by a microscope point technique with adjustments made by weight per area constants (WAC) (3). These estimates were compared with the known composition of ingesta and some of the possible sources of error in manual separation were examined.…”
Section: Introductionmentioning
confidence: 99%